Pulmonary hypertension: modern methods of treatment and ways of their long-term development - Anna V. Zagrebelnaya; Liliya V. Korokina; Tatyana N. Malorodova; Olesya V. Shcheblykina; Tatyana V. Avtina; Anton А. Bolgov; Elena S. Malyutina; Vladislav I. Simonov; Vladislav A. Travkin; Artem А. Dmitriev; Amonullo A. Aripov; Dmitry V. Shcheblykin (Belgorod National Research University, 2023)
Introduction: The purpose of this work is to review the main pathogenetic mechanisms of the development of PH, as well as modern established methods of treatment of various types of PH and to consider new, most relevant and promising possibilities of therapy for this pathology. Etiology, pathogenesis and epidemiology: In the modern structure of diseases, pulmonary hypertension plays a significant role, affecting about 1% of the population. However, each of its five main groups has its own characteristics. The causes of pulmonary hypertension can be a polyetiological violation of the processes of endotheliocyte apoptosis and angiogenesis, passive transmission of increased pressure from the left heart to the small circulatory system, chronic hypoxia, leading to vascular remodeling, and many others. In general, it is worth noting that, despite the multiplicity of etiological factors, the main pathogenetic link in the development of pulmonary hypertension is endothelial dysfunction. Treatment and promising areas of research: This article discusses the main established approaches to the treatment of pulmonary hypertension: general recommendations for patients, drugs used as supportive nonspecific therapy, as well as specific conservative and radical methods of treatment. In addition, the main modern directions of scientific research in the field of treatment of pulmonary hypertension are described. Such promising methods as the use of stem cells, gene therapy and epigenetic drugs are considered. Conclusion: Despite active research and many different drugs intended for the treatment of pulmonary hypertension, this pathological condition remains an urgent health problem. Thus, the search for new points of application of therapy and fundamentally new methods of treatment of pulmonary hypertension remains relevant to this day.